HUBUNGAN KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET ZAT BESI DENGAN STATUS ANEMIA SELAMA KEHAMILAN DI PUSKESMAS SEI PANCUR KOTA BATAM TAHUN 2017 - Gaol, Nurlela Lumban; Mariyana, Mariyana (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
WHO informs that incidence of anemia. Its incidence is around 20 to 89% with 11g%Â  (g/dl) standard. Anemic pregnancy in Indonesia shows high rates, they are 3.8% on first trimester, 13.6% on second trimester and 24.8% on third trimester. 70% pregnant women in Indonesia have anemia due to poor nutrition. This study is to know the correlation between adherence to take Fe tablets and anemia status during pregnancy at SeiPancurHelath Center of Batam City in 2017. This study was analytical survey with cross sectional approach. Data collection was done through questionnaire distribution and Hb test. The sampling technique was accidental sampling on 40 respondents. The study was conducted on June 2017 in which data analysis was through chi square. 17,5% respondents were discipline while the rest (82.5%) were not. 70% respondents got anemia whereas another 30% did not. There was correlation between adherence to take Fe tablets and anemia status during pregnancy at SeiPancurHelath Center of Batam City in 2017 with p value 0.006 < 0.05.